Transcriptomic analysis of crustacean molting gland (Y-organ) regulation via the mTOR signaling pathway - S. Shyamal (Nature Portfolio, 2018)
Abstract The intermolt crustacean Y-organ (YO) maintains a basal state mediated by pulsatile release of molt inhibiting hormone (MIH), a neuropeptide produced in the eyestalk ganglia, inhibiting YO ecdysteroidogenesis. Reduction of MIH results in YO activation and the animal enters premolt. In the crab, Gecarcinus lateralis, molting was induced by eyestalk ablation (ESA). ESA animals were injected with either rapamycin, an mTOR inhibitor, or DMSO vehicle at Day 0. YOs were harvested at 1, 3, and 7 days post-ESA and processed for high throughput RNA sequencing. ESA-induced increases in mRNA levels of mTOR signaling genes (e.g., mTOR, Rheb, TSC1/2, Raptor, Akt, and S6 kinase) declined following rapamycin treatment. In concert with mTOR inhibition, mRNA levels of ecdysteroid biosynthesis genes (e.g., Nvd, Spo, Sad, Dib, and Phm) were decreased and accompanied by a decrease in hemolymph ecdysteroid titer. By contrast, rapamycin increased the mRNA level of FKBP12, the rapamycin-binding protein, as well as the mRNA levels of genes associated with Wnt and insulin-like growth factor signaling pathways. Many MIH and transforming growth factor-β signaling genes were down regulated in ESA animals. These results indicate that mTOR activity either directly or indirectly controls transcription of genes that drive activation of the YO.